Source-to-sink processes and genetic mechanism of progradational and lateral accretion submarine fans in the Qiongdongnan Basin, South China Sea - Congjun Feng; Guozhang Fan; Zhili Yang; Xingzong Yao; Xinglei Song; Weiqiang Li; Hongjun Qu; Qiang Zhang; Xuefeng Wang (Frontiers in Marine Science, 2024)
Submarine fan reservoirs are important accumulation zones for oil, gas, and natural gas hydrates, offering significant potential for hydrocarbon exploration. During the deposition period of the Sanya Formation in the southern part of the Changchang Sag of the Qiongdongnan Basin, a large submarine fan developed. However, the internal structure, source-sink system, and formation mechanism of this fan remain poorly understood, posing significant challenges to exploration in this area. This paper examines the source-to-sink sedimentary processes and deposition of submarine fans, using the Changchang Sag, in the Qiongdongnan Basin in the Northern South China Sea, as an example, which will provide valuable general guidance for deep water oil and gas exploration. Based on the theories of seismic stratigraphy and seismic sedimentology, this paper utilizes techniques such as seismic facies analysis, seismic attribute optimization, paleogeomorphology reconstruction, and source-to-sink sedimentary system analysis to analyze the 3D seismic data of the study area. Research indicates that the Sanya Formation in the Changchang Sag of the Qiongdongnan Basin comprises three depositional units: submarine fan, feeder channel, and Semi-deep marine to deep marine mudstone. The submarine fan is a fan formed by the coupling and convergence of submarine fans sourced from the southwest and southeast. Internally, it is divided into three sub-facies: the proximal fan of the sand-rich submarine fan, the main body of the sand-rich submarine fan lobes, and the distal lobes of the sand-rich submarine fan. The submarine fan sourced from the southwest extends nearly north-south and is primarily fed by sediment transported through three large, banded ancient valleys. The sedimentary filling is characterized by three-phase progradation. The submarine fan sourced from the southeast extends nearly east-west and is primarily fed by sediment transported through a single large, banded ancient valley. The sedimentary filling is characterized by two-phase lateral accumulation. During the deposition period of the Sanya Formation, certain areas of the southern uplift belt were exposed for extended periods and subjected to weathering and erosion. Sediments are transported to large ancient valleys through small supply channels. A large number of sediments were transported to the southern slope of the Changchang sag through the provenance channel system such as large ancient valleys and slope belts and deposited in the center of the sag. These make up a complete system of large ancient uplifts and submarine fan source-to-sink sedimentary systems.The sedimentary model is a lobed submarine fan controlled by semi-restricted ancient valleys and expansive basins.

Deciphering the degradation characteristics of the fungicides imazalil and penflufen and their effects on soil bacterial community composition, assembly, and functional profiles - Lingxi Han; Han Xu; Qianwen Wang; Xiaoli Liu; Xiaoming Li; Yiran Wang; Jiyun Nie; Mingyu Liu; Chao Ju; Congjun Yang (Journal of Hazardous Materials, 2023)

Identification of Isthmin1 in the small annual fish, Nothobranchius guentheri, as a novel biomarker of aging and its potential rejuvenation activity - Congjun Li; Lili Song; Yang Zhou; Jiangshui Yuan; Shicui Zhang (Biogerontology, 2022)

Lithology and oil-bearing properties of tight sandstone reservoirs: Chang 7 member of Upper Triassic Yanchang Formation, southwestern Ordos Basin, China - Congjun Feng; Hua Yang; Renhai Pu; Yaning Wang; Daxing Wang; Xiaowei Liang; Mengbo Zhang; Yougen Huang; Shixiang Fei (Geosciences Journal, 2017)